2021
DOI: 10.1007/s12519-021-00478-1
|View full text |Cite
|
Sign up to set email alerts
|

Physicians’ perspectives on adverse drug reactions in pediatric routine care: a survey

Abstract: Background Children and adolescents are at particular risk for adverse drug reactions (ADRs). We investigated physicians’ perceptions on ADRs in pediatric routine care. Methods In this exploratory study from April to November 2020, we invited physicians treating pediatric patients across Germany to complete an online questionnaire consisting mainly of closed questions. Results Completion rate was 98% (127/129). Of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
0
4
0
2
Order By: Relevance
“…As a result, physicians are confronted with a dilemma when it comes to making treatment decisions, in which both the demand for evidence-based treatment and liability issues have to be taken into account. However, it is not only about legal consequences: In a survey among physicians treating pediatric patients, more than 80% of physicians reported that it is very important to them to talk to parents about potential adverse drug reactions when a drug is used off-label compared to 38% of physicians who reported this for commonly used authorized drugs [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, physicians are confronted with a dilemma when it comes to making treatment decisions, in which both the demand for evidence-based treatment and liability issues have to be taken into account. However, it is not only about legal consequences: In a survey among physicians treating pediatric patients, more than 80% of physicians reported that it is very important to them to talk to parents about potential adverse drug reactions when a drug is used off-label compared to 38% of physicians who reported this for commonly used authorized drugs [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was similar to previous observations [ 12 , 13 ]. Despite having such a good knowledge of PV and ADR, the neurologists participating in our study were unaware of the existence of pharmacotherapy safety monitoring centers responsible for PV in their countries [ 14 ]. Similar conclusions were reached by researchers from Malaysia, who confirmed that this was the main reason (40%) for not reporting ADRs [ 15 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In einer deutschlandweiten Onlinebefragung von Ärzten, die Kinder und Jugendliche behandeln, berichteten 23 % der Befragten, dass sie nicht einschätzen können, bei wie vielen ihrer pädiatrischen Patienten unter einer Arzneimitteltherapie UAW auftreten [12]. Als häufigste Ursachen für UAW wurden von den Teilnehmern das Wirkstoffprofil (65 %) sowie Disposition des Patienten (genetisch/ zugrundeliegende Erkrankung, 35 %) genannt.…”
Section: Einschätzungen Von äRzten Zu Uaw In Der Pädiatrieunclassified
“…Als häufigste Ursachen für UAW wurden von den Teilnehmern das Wirkstoffprofil (65 %) sowie Disposition des Patienten (genetisch/ zugrundeliegende Erkrankung, 35 %) genannt. Auffällig war, dass sich die Antworten der Ärzte, die in der Neuro-und Sozialpädiatrie arbeiten und daher häufig Antikonvulsiva verordnen, von denen der anderen Teilnehmer unterschieden: Dosiserhöhung (68 %) und Arzneimittelinteraktionen (47 %) wurden von dieser Ärztegruppe deutlich häufiger als von den restlichen Befragten als Ursachen für UAW genannt [12]. Dies spiegelt auch die Tatsache wider, dass in der Neuropädiatrie häufig aufgrund von Therapieversagen statt einer Monotherapie eine Kombinationstherapie angesetzt werden muss [13].…”
Section: Einschätzungen Von äRzten Zu Uaw In Der Pädiatrieunclassified